Association between order of eating and thinness among preschool children in Taizhou, China: a cross-sectional study - Yang, Jingyun; Huang, Yao; Wu, Huilan; Wu, Yixin; Wang, Yun; Fan, Hailing; Chen, Mengjia; Wang, Lizhen; Zhang, Meixian (Frontiers in Pediatrics, 2025)
BackgroundOrder of eating is reportedly associated with childhood obesity. However, few studies have examined the relationship between the order of consumption of vegetables and meat/fish and childhood thinness. We aimed to investigate the effect of the order of consumption of meat/fish and vegetables on the risk of thinness in preschool children.MethodsFrom December 1, 2021, to January 31, 2022, 419 thinness and 1,204 normal-weight preschool children were selected from kindergartens in Taizhou, China. We used a questionnaire to determine whether the children ate vegetables or meat/fish first at mealtimes and analyzed the association between the first food consumed and children's thinness status.ResultsOverall, 53.4% and 46.6% of the children ate vegetables and meat/fish first, respectively. The percentage of eating vegetables first was higher in children with thinness than that in normal weight (58.95% vs. 51.41%, P = 0.008). After adjusting for sex, parental education and parental BMI category, the odds ratio for being thin was 1.280 for children who ate vegetables first (95% confidence interval: 1.016–1.612, P = 0.036) compared with those who ate meat/fish first.ConclusionsOur study revealed that order of eating was associated with childhood thinness among preschool children. For children with thinness, we do not recommend that they eat vegetables first, but rather encourage them to eat meat/fish first.